Anti-PM/Scl Antibody-positive Systemic Sclerosis Complicated by Multiple Organ Involvement - Shimizu, Tatsuya (Intern Med, 2020)
A 40-year-old Japanese woman developed malignant-phase hypertension complicated by thrombotic microangiopathy, progressing to end-stage renal disease. Five years later, she was diagnosed with pulmonary arterial hypertension and interstitial pneumonia. Despite a lack of overt skin sclerosis, nucleolar staining in our indirect immunofluorescence analysis and nailfold capillaroscopy facilitated the diagnosis of anti-PM/Scl antibody-positive systemic sclerosis. We observed the persistent presence of anti-PM/Scl antibodies throughout the clinical course, suggesting that her kidney disease was scleroderma renal crisis. Anti-PM/Scl antibodies can be associated with multiple organ diseases. Careful attention to a patient's antinuclear antibody pattern and dermatological findings may help clarify the etiology of undiagnosed diseases.